2006
DOI: 10.1177/0731684406065133
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Shear on the Deflection of Simply Supported Composite Beam Loaded Linearly

Abstract: In this study two deflection functions due to both the flexure and the shear of an orthotropic simply supported beam loaded linearly are obtained by means of the anisotropic elasticity theory. In order to see the effect of shear, the deflections are calculated for different fiber directions. Two different composite materials are used during the deflection analysis. The error level and the shear deflection for the thermoplastic composite beam are the smallest for 45 orientation angle, and that for the polymer-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Building upon this approach, exact solutions for laminated beams were developed by Silverman [5], Hasin [6], Gerstner [7], Rao and Ghosh [8] and Cheng et al [9]. Additionally, Esendemir et al [10] developed an analytical solution based on elasticity for bending analysis of beam structures. Analyzing laminated systems within the framework of elasticity poses a significant challenge in developing an analytical solution that accounts for arbitrary boundary conditions due to the complexity of these systems and computational difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon this approach, exact solutions for laminated beams were developed by Silverman [5], Hasin [6], Gerstner [7], Rao and Ghosh [8] and Cheng et al [9]. Additionally, Esendemir et al [10] developed an analytical solution based on elasticity for bending analysis of beam structures. Analyzing laminated systems within the framework of elasticity poses a significant challenge in developing an analytical solution that accounts for arbitrary boundary conditions due to the complexity of these systems and computational difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Also, investigations of the effect of shear on the deflection in simply supported composite beams have been recently carried out. [13][14][15] In a general review of material evaluation bending tests, Mullin and Knoell 16 discussed the theoretical origins of L t ratios (where L is the span length and t is the nominal thickness) and the effects of material variables and specimen defects such as voids. Westwater 17 observed that specimens with small L t ratios often fail by cracks running out to, or past, the support nose and also that the amount of overhang may affect the mode of failure.…”
Section: Introductionmentioning
confidence: 99%
“…Also, investigations of the effect of shear on the deflection in simply supported composite beams have been recently carried out. 1315…”
Section: Introductionmentioning
confidence: 99%
“…Using these Airy stress polynomial functions approach, Silverman [5], Hasin [6], Gerstner [7], Rao and Ghosh [8] and Cheng et al [9] developed exact solutions for laminated beams. An elasticity-based analytical solution for the bending analysis of beam structures is developed by Esendemir et al [10].…”
Section: Introductionmentioning
confidence: 99%